Місце народження Володимира Грінченка - Граб, В.І. (Археологія, 2014)
Виправлено помилку щодо місця народження В.А. Грінченка. В биографии археолога Владимира Автономовича Гринченко (1900—1948) указывают место его рождения — с. Мохуровка на Полтавщине. Действительно, оно фигурирует в протоколе допроса ученого. Но автор обратил внимание, что такой населенный пункт не значится в справочной литературе и архивных документах. Видимо, название села появилось изза неразборчивого произношения пытаемого ученого и/или неграмотности палачей. Поиски привели автора к Домовой книге по последнему месту жительства В.А. Гринченко — г. Полтава, ул. Верховинца, дом 10, в которой указано место его рождения: хут. Цокуровка Диканьского рна Полтавской обл. Домовая книга дала ответ и на вопрос, почему ученый поселился здесь. Исходя из отчества (а оно редкое), в доме жили две его сестры и, что важно, также уроженки хут. Цокуровка на Полтавщине. Таким образом, есть все основания считать, что В.А. Гринченко родился на хут. Цокуровка недалеко от с. Ве ликая Рудка ныне Диканьского рна Полтавской обл. Mokhurivka village in Poltava region is indicated in the archaeologist volodymyr avtonomovych Hrinchenko’s biography (1900—1948). indeed, it appears in protocol of the interrogation with the researcher. However, the author has paid attention to the fact that there is no such settlement in reference literature and archive documents. apparently, the name of the village appeared owing to the indecipherable pronunciation of the tortured scholar and\or ignorance of the executioners. searching led the author to the houseregister of v.a. Hrinchenko’s last place of life: Poltava, 10, verkhovyntsia st. in this book, the place of his birth is indicated as following: tsukorivka hamlet in Dykanka Region of Poltava Oblast. House register also allows answering the question why the scholar settled here. coming from the patronymic, which is rare, his two sisters lived in that house, and they also, and this is important, were born in tsukorivka hamlet in Dykanka Region of Pol tava Oblast. consequently, there are all reasons to consider that v.a. Hrinchenko was born in tsukorivka hamlet not far from velyka Rudka village of today Dykanka Region in Poltava Oblast.